Comparative evaluation of Russian’s regions innovation capacity - V. Rokotyanskaya, Violetta (2018)
The economy of regions needs cardinal increase in efficiency of use of innovative potential, stimulation of scientific research, creation of effective system of commercialization of results of scientific activity. In work the analysis of genesis of the concepts «innovation», «innovative potential», «innovative activity» is carried out; methodological bases of assessment of innovative potential and innovative activity at the regional level are investigated and the system of indicators of their assessment is developed; to carry out the analysis of innovative potential and innovative activity of regions of the Southern and North-Caucasian federal districts; organizational, financial and standard and legal factors of state regulation of innovative activity of the region are offered.